(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The article considers the modeling of the process for studying the heat and mass transfer of sludge in a gas jet and develops an acceptable mathematical model for the installation of forced removal and condensation of the vapor-air mixture and calculations in an integrated automatic design system of the ChemCad type. The mathematical model consists of five equations. The numerical solution of the system gives the temperature distribution in the drop during its separation into components.